2019
DOI: 10.3390/en12193718
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the Energy Efficiency of EU Member States: The Potential of Energy Recovery from Waste in the Circular Economy

Abstract: This paper examines energy efficiency across 28 selected European Union (EU) Member States and reviews the potential for energy recovery from waste according to the efficiency scores obtained. The efficiencies are assessed through data envelopment analysis (DEA) and the following variables are used, inputs: final energy consumption, labour, capital, population density and outputs: gross domestic product (GDP), nitrogen oxide (NOx) emissions, sulphur oxide (SOx) emissions and greenhouse gas (GHG) emissions for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 72 publications
(102 reference statements)
0
26
0
Order By: Relevance
“…In the EU waste management hierarchy, waste management is ranked as follows: waste prevention, preparation for re-use, recycling, and recovery, with landfilling being the last resort. The need to efficiently treat the waste is in some countries, including Slovakia, enormous [19]. However, the CE concept is also adopted by developing countries [5,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…In the EU waste management hierarchy, waste management is ranked as follows: waste prevention, preparation for re-use, recycling, and recovery, with landfilling being the last resort. The need to efficiently treat the waste is in some countries, including Slovakia, enormous [19]. However, the CE concept is also adopted by developing countries [5,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The bibliometric effort identified that several issues related to the circular economy have attracted the attention amongst researchers [76,82,103,122]. This identification has shown the relevance of studies performed in these fields and the enormous potential to be explored in future work.…”
Section: Discussionmentioning
confidence: 99%
“…Circular economy approaches may promote positive externalities [120] and economic growth [121]. The reverse is also true, where the economic and financial stabilities may create conditions for a more sustainable development [122]. These positive impacts are, for example, particularly relevant in agriculture, where the reuse of agro-waste [123] or waste from other sectors and activities [124] may improve the narrow margins of profit of the sector and bring alternatives for waste management [125].…”
Section: Economic Sectorsmentioning
confidence: 99%
“…Regarding energy efficiency improvements, Wang et al (2019) compared the CO 2 emissions in relation to GDP growth from 25 countries and found that India and China are the two worst countries in terms of energy efficiency [54]. A similar study focusing on energy recovery from waste for European Union (EU) member states was produced by Halkos and Petrou (2019) [47]. Furthermore, Robaina-Alves et al (2015) derived the efficiencies of European countries based on the maximization of the ratio between the GDP (desired output) and GHG emissions (undesired output) [52].…”
Section: Literature Review-energy-related Country Comparisons With Damentioning
confidence: 99%
“…Out of the 25 studies analyzed (including the present one), 15 of them (60%) use the same set of inputs: labor force, capital stock and energy consumption [34,39,40,42,44,[47][48][49][50][52][53][54]56,57,59]. Furthermore, out of these 15 studies, four consider only the GDP as an output [44,49,53,56], while the rest consider the GDP as a desirable output and GHG emissions as an undesirable output [34,39,40,42,47,48,50,52,54,57,59]. Within DEA country comparisons, efficiency is, therefore, usually measured as a minimization of the labor force, capital stock, and energy consumption (inputs) in order to maximize the GDP (desirable output) and minimize the GHG emissions (undesirable output).…”
Section: Literature Review-energy-related Country Comparisons With Damentioning
confidence: 99%